Construction of a Road Network in Central Surabaya And Traffic Conditions in The Girilaya Road Surabaya City Based on Geographic Information Systems - Arip Widarto; farida hardaningrum (NAROTAMA UNIVERSITY, Indonesia, 2022)
The purpose of this study was to create a road network in the form of a geographic information system and to find out the traffic conditions that occurred on the Girilaya road, Surabaya City in 2021. This traffic condition research used a method that refers to the calculation of congestion figures. In accordance with field observations, the road with the type of road 2/2 UD is two lanes – two-way undivided, with a road width of 6 meters for a total of 2 directions with a shoulder of 1 meter each on the right and left sections. The facilities on these roads are not equipped with traffic signs such as (no stopping, no parking, speed limit). The highest average daily traffic volume on this road segment is from 07.00 – 18.00 as many as 1725.8 vehicles/hour. Motorcycles are the most dominant type of vehicles passing through these roads. From the analysis of the level of congestion carried out, the results showed that the side barriers on the road segment were categorized as moderate (M) at 378.6 events/hour. Congestion occurs because of the density of activities and vehicles reduce speed and stop on the side of the road. This results in the value of service on the road section being D indicating that the flow of vehicles is obstructed, the speed is low and the volume of vehicles is above capacity. Therefore, the role of the government is very important to reduce the level of congestion that occurs and drivers are more orderly in carrying out activities on these roads.